Etoposide induces pancreatic β-cells cytotoxicity via the JNK/ERK/GSK-3 signaling-mediated mitochondria-dependent apoptosis pathway. (October 2016) - Lee, Kuan-I; Su, Chin-Chuan; Yang, Ching-Yao; Hung, Dong-Zong; Lin, Ching-Ting; Lu, Tien-Hui; Liu, Shing-Hwa; Huang, Chun-Fa
Abstract: Etoposide is widely used in the treatment of the different types of tumors such as pancreatic cancer. However, etoposide also causes several unwanted side-effects in normal viable cells, including pancreatic β-cells, which are vulnerable to chemical-induced injuries, and the molecular mechanisms underlying etoposide-induced apoptosis are still unclear. Here, the results showed that in RIN-m5F cells (a β-cell-derived cell line), the number of viable cells was significantly decreased after 24 h of etoposide treatment and underwent mitochondria-dependent apoptotic signals accompanied by mitochondrial dysfunction, and increases in the population of sub-G1 hypodiploid cells and apoptotic cells, caspase-3 activity, and the activation of caspase cascades. Etoposide also increased the phosphorylation levels of glycogen synthase kinase (GSK)-3α/β in treated RIN-m5F cells. Pretreatment with LiCl, a GSK-3 inhibitor, prevented etoposide-induced mitochondria-dependent apoptosis and GSK-3 protein phosphorylation in RIN-m5F cells. Furthermore, exposure of the cells to etoposide induced the phosphorylation of c-Jun N-terminal kinase (JNK) and extracellular signal-related kinase (ERK)1/2 but not p38-MAPK, which was suppressed by the specific JNK inhibitor (SP600125) and ERK1/2 inhibitor (PD98059), respectively. Additionally, pretreatment with both SP600125 and PD98059 effectively suppressed etoposide-induced β-cell cytotoxicity, apoptosis, and GSK-3 protein phosphorylation; however, LiCl did not reverse JNK and ERK1/2 phosphorylation. Taken together, these results suggest that etoposide is capable of causing cytotoxicity on pancreatic β-cells by inducing apoptosis through the JNK/ERK-mediated GSK-3 downstream-triggered mitochondria-dependent signaling pathway. Graphical abstract: Highlights: Etoposide induced cytotoxicity in pancreatic β-cells by apoptosis. Etoposide caused GSK-3-mediated mitochondria-dependent apoptotic signals. JNK/ERK signals-mediated GSK-3 was involved in etoposide-induced β-cell apoptosis.